6(-2x-8)=-96

Simple and best practice solution for 6(-2x-8)=-96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-2x-8)=-96 equation:


Simplifying
6(-2x + -8) = -96

Reorder the terms:
6(-8 + -2x) = -96
(-8 * 6 + -2x * 6) = -96
(-48 + -12x) = -96

Solving
-48 + -12x = -96

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + -12x = -96 + 48

Combine like terms: -48 + 48 = 0
0 + -12x = -96 + 48
-12x = -96 + 48

Combine like terms: -96 + 48 = -48
-12x = -48

Divide each side by '-12'.
x = 4

Simplifying
x = 4

See similar equations:

| -4z(-5z-10)-4(-2z-9)= | | 25.8+z=30.6 | | 2(-7x+8)=72 | | 2(-7c+8)=72 | | .16x+.50x+x=120 | | y=1/2(1)-2 | | (v+4)(v+6)=0 | | y=1/2(0)-2 | | -6x-6=-6+2x | | 4x+27=6x | | y=1/2(-2)-2 | | y=1/2(-4)-2 | | 10+5x=4x+64 | | 12x-7=10x+13 | | -8-4n=19 | | 2y-6=5y+9 | | 9p^3+73p+70=0 | | y=-1/4(-2)-6 | | x^2-y^2=41 | | -26=5x+9 | | -49+3y+9=2(3y-4)-8 | | 10+5x=-4x+64 | | 10n^2-29n+10=0 | | 13a-13=14a+5 | | -2m-7=-29 | | y=-1/4(-4)-6 | | 8x+13=53 | | 72=-8(r-2) | | a-b=7 | | 3.7x-8.5=13.7 | | y=-1/4(5)-6 | | 2x^2+27x-7.5=0 |

Equations solver categories